1998
DOI: 10.1016/s0735-1097(98)00325-8
|View full text |Cite
|
Sign up to set email alerts
|

Patients treated by cardiologists have a lower in-hospital mortality for acute myocardial infarction

Abstract: Treatment by a cardiologist is associated with approximately a 17% reduction in hospital mortality in acute myocardial infarction patients. In addition, patients of physicians treating a high volume of patients have approximately an 11% reduction in mortality. This has important implications for the optimal treatment of acute myocardial infarction in the current transformation of the health care delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
48
2
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 13 publications
7
48
2
4
Order By: Relevance
“…After accounting for differences in case mix, we found that patients receiving care from higher-caseload nephrologists had greater mortality than those receiving care from lower-caseload nephrologists and that this association was robust in both categorical and restricted cubic spline analyses. The findings contrast with those of prior studies showing an inverse association between provider caseload and patient outcomes in the context of surgical 12,21 and invasive cardiovascular 11 procedures and medical conditions (e.g., acute myocardial infarction, 8 sepsis, 9 pulmonary embolus, 14 and AIDS 13 ). In a systematic review evaluating the effect of physician volume on outcomes, 69% of studies showed that high provider volume was a determinant of improved patient outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…After accounting for differences in case mix, we found that patients receiving care from higher-caseload nephrologists had greater mortality than those receiving care from lower-caseload nephrologists and that this association was robust in both categorical and restricted cubic spline analyses. The findings contrast with those of prior studies showing an inverse association between provider caseload and patient outcomes in the context of surgical 12,21 and invasive cardiovascular 11 procedures and medical conditions (e.g., acute myocardial infarction, 8 sepsis, 9 pulmonary embolus, 14 and AIDS 13 ). In a systematic review evaluating the effect of physician volume on outcomes, 69% of studies showed that high provider volume was a determinant of improved patient outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…First, it has been hypothesized that provider caseload may be a proxy for a physician's experience, knowledge, skills, and/or quality of care with which to manage particular diseases. 8,9,13 Second, there may be a selection factor in which (1) physicians who achieve favorable patient outcomes will receive more patient referrals or (2) patients may self-refer to physicians who care for patients with similar characteristics. 9,10 Third, these observations may reflect not only physician practice patterns but also the system in which the provider works.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Similarly, patients with unstable angina are less likely to receive effective treatments if treated by generalists rather than cardiologists. 7,8 In addition, compared with generalists, cardiologists are less likely to order tests but prescribe more medications for hypertension and ischemic heart disease.…”
mentioning
confidence: 99%